PENGGUNAAN PERAGA VISUAL PADA PROGRAM PENGABDIAN MASYARAKAT DI WILAYAH PESISIR DAN KEPULAUAN RAWAN BENCANA - Wardani, Abellia Anggi, Dr.; Kumala, Anin N; Windah, Caroline A; Shintya, Shintya (Bhakti: Jurnal Pengabdian Masyarakat, 2025)
Indonesia’s coastal and archipelagic regions are vulnerable to disasters such as earthquakes, tsunamis, and floods. In this context, community service activities require participatory and educational approaches that are easily understood by people of various ages and backgrounds. This article discusses the use of visual aids—such as infographics, leaflets, animated videos, illustrations, and x-banners—as tools for disaster education. Through a literature review of four articles on community service programs, this study finds that visual aids are effective in increasing disaster risk awareness, reinforcing visual memory of mitigation procedures, and engaging vulnerable groups such as children and indigenous communities. This approach also enables the integration of local knowledge into culturally and regionally grounded risk reduction strategies. The article recommends the use of visual methods as a transformative strategy for disaster education in coastal and island areas.